2022
DOI: 10.18502/ijph.v51i3.8941
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Standardized Prevalence of Corneal Opacity and Its Determinants; Tehran Geriatric Eye Study (TGES)

Abstract: Background: We aimed to determine the age and sex standardized prevalence of corneal opacity and its determinants Methods: The Tehran Geriatric Eye Study (TGES) is a population-based cross-sectional study conducted on 3791 subjects aged above 60 yr in Tehran, Iran (2019) selected using stratified random cluster sampling. After sampling, all subjects underwent complete ophthalmic, optometric, and eye examinations. Results: The 3310 participated in the study, of whom the data of 3284 were analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Additionally, studies conducted in India in 2015 among the rural Indian population and in 2016 among the rural population in Bihar reported 3.7% and 2.35% CO, respectively 32 33. Similarly, the findings of the present study were greater than those of a population-based study and the Tehran Geriatric Eye Study (TGES) in 2017 and in 2022 in Iran, which showed 1.68% and 9.58%, respectively, of CO 12 24. In addition, studies conducted by Mahdi et al 34 and Durkin et al 35 reported 4.1% and 1.3%, respectively, of CO; these findings were also lower than our findings.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Additionally, studies conducted in India in 2015 among the rural Indian population and in 2016 among the rural population in Bihar reported 3.7% and 2.35% CO, respectively 32 33. Similarly, the findings of the present study were greater than those of a population-based study and the Tehran Geriatric Eye Study (TGES) in 2017 and in 2022 in Iran, which showed 1.68% and 9.58%, respectively, of CO 12 24. In addition, studies conducted by Mahdi et al 34 and Durkin et al 35 reported 4.1% and 1.3%, respectively, of CO; these findings were also lower than our findings.…”
Section: Discussionsupporting
confidence: 41%
“…Several previous studies in different parts of the world estimated the prevalence of CO as depicted in a comparison table for further information (online supplemental table 4). 12 24 25 30–37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…Corneal opacities represent a leading cause of blindness worldwide 1 . As shown by Hashemi et al in patients above 60 years of age, the prevalence of corneal opacities in at least one eye is 9.58% 2 .…”
Section: Introductionmentioning
confidence: 87%